Menilai Efektivitas Penegakan Hukum Persaingan Usaha terhadap Penyalahgunaan Posisi Dominan di Industri Penerbangan Indonesia (Lion Air Group) - Salsabila Adira Balqis (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study discusses allegations of abuse of dominant position by Lion Air Group in the domestic aviation market and air cargo services in Indonesia. By controlling more than 50% of the market share, the group is suspected of unilaterally setting ticket prices and logistics costs, which could hinder healthy business competition and harm consumers and competing airlines. This study uses a normative juridical approach with a descriptive qualitative analysis method, supported by secondary data from legislation, KPPU reports, and academic literature related to competition law. The study's findings indicate that the concentrated market structure and weak regulatory oversight contribute to the formation of dominant behavior that harms the market and consumers. Legally, such actions violate Article 25 of Law Number 5 of 1999, as they result in discriminatory practices and unreasonable price control. Synergy between the KPPU and the Ministry of Transportation is needed to strengthen regulations in the aviation sector in order to create a business climate that is more fair, competitive, and oriented towards public welfare.